An Anti-CD34 Antibody-Functionalized Clinical-Grade POSS-PCU Nanocomposite Polymer for Cardiovascular Stent Coating Applications: A Preliminary Assessment of Endothelial Progenitor Cell Capture and Hemocompatibility - Tan, Aaron (Public Library of Science, 2013)
In situ endothelialization of cardiovascular implants has emerged in recent years as an attractive means of targeting the persistent problems of thrombosis and intimal hyperplasia. This study aimed to investigate the efficacy of immobilizing anti-CD34 antibodies onto a POSS-PCU nanocomposite polymer surface to sequester endothelial progenitor cells (EPCs) from human blood, and to characterize the surface properties and hemocompatibility of this surface. Amine-functionalized fumed silica was used to covalently conjugate anti-CD34 to the polymer surface. Water contact angle, fluorescence microscopy, and scanning electron microscopy were used for surface characterization. Peripheral blood mononuclear cells (PBMCs) were seeded on modified and pristine POSS-PCU polymer films. After 7 days, adhered cells were immunostained for the expression of EPC and endothelial cell markers, and assessed for the formation of EPC colonies. Hemocompatibility was assessed by thromboelastography, and platelet activation and adhesion assays. The number of EPC colonies formed on anti-CD34-coated POSS-PCU surfaces was not significantly higher than that of POSS-PCU (5.0±1.0 vs. 1.7±0.6, p>0.05). However, antibody conjugation significantly improved hemocompatibility, as seen from the prolonged reaction and clotting times, decreased angle and maximum amplitude (p<0.05), as well as decreased platelet adhesion (76.8±7.8 vs. 8.4±0.7, p<0.05) and activation. Here, we demonstrate that POSS-PCU surface immobilized anti-CD34 antibodies selectively captured CD34(+) cells from peripheral blood, although only a minority of these were EPCs. Nevertheless, antibody conjugation significantly improves the hemocompatibility of POSS-PCU, and should therefore continue to be explored in combination with other strategies to improve the specificity of EPC capture to promote in situ endothelialization.